A Method and Algorithm for Stabilizing the Output State of an Optical Transceiver (2012)
The invention relates to a method and algorithm for stabilizing the output state of an optical transceiver. The method includes comparing a signal quality monitor (SQM) register value with a predetermined threshold. If the SQM register value is less than or equal to the predetermined threshold, a microcontroller unit (MCU) reads and determines the rx_lol state bit value of a clock and data recovery (CDR) chip. If the rx_lol state bit value reaches a low logic level value at least 3 times, the MCU converts the state bit values of rx_lol and mod_nr into low logic level values, or else, convert the state bit values of rx_lol and mod_nr into high logic level values. If the SQM register value is greater than the predetermined threshold then the state bit values of rx_lol and mod_nr will be left unchanged. When there is no data input to the CDR chip, the method of the present invention will maintain rx_lol and mod_nr at high or low logic level values to stabilize the output state of the optical transceiver.